HUBUNGAN DUKUNGAN SOSIAL DAN KEPERCAYAAN DIRI DENGAN PRESTASI BAHASA INGGRIS SISWA KELAS VIII SMP NEGERI 6 BOYOLALI - Woro Kusrini; Nanik Prihartanti (Universitas Muhammadiyah Surakarta, 2014)
This study deals with the relationships of social support and self confidence with the English language achievement of eight grade students of State Junior High School 6 Boyolali. The purpose of this study was to determine (1) the relationship of social sup- port and confidence with the English language student achievement; (2) the relation- ship of social support to the achievement of English language students, and (3) the relationship of confidence with the English language student achievement. The popula- tion of this study was all eighth grade students of State Junior High School 6 Boyolali, amounting to 201 students and the number of samples were 132 students taken by proportional random sampling technique. This study uses the method of documentation and questionnaire as data collection technique, while the technique of data analysis in this study was the Pearson correlation and multiple linear. The results showed as fol- lows: (1) there is a relationship of social support and self confidence with the English language student achievement (F-test = 222.948); (2) there is a relationship of social support to the students’ English achievement (r = 0.445 with p0.05); (3) there is a relationship of self confidence with the English language student achievement (r = 0.445 with p0.05).